Coexistence of low-grade pulmonary mucinous epithelioid carcinoma and metastatic adrenal sarcomatoid carcinoma: a rare case report with BRAF p.V600E-driven molecular insights and clinical challenges - Xu, Guangyan; Zou, Fan; Lan, Yuanbo (Frontiers in Oncology, 2025)
IntroductionPulmonary mucinous epithelioid carcinoma (PMEC) is a rare malignancy that typically progresses slowly and has a favorable prognosis. In contrast, adrenal sarcomatoid carcinoma (ASC) is an aggressive and uncommon cancer with poor outcomes. The coexistence of low-grade PMEC and metastatic ASC is exceedingly rare and presents unique clinical challenges, with limited treatment options and poor prognosis. This case report highlights the diagnosis and management of a patient with long-term, slow-progressing low-grade PMEC and rapidly progressing metastatic ASC.Case presentationA 44-year-old male with a 20-year history of intermittent respiratory symptoms developed abdominal pain and imaging findings indicative of adrenal metastasis and multiple bone metastases. Initial diagnosis through CT and PET-CT scans raised suspicion for pulmonary tumors, and subsequent biopsies confirmed low-grade PMEC in the lungs. In 2023, further diagnostic work revealed a sarcomatoid carcinoma (SC) in the left adrenal gland. Molecular testing revealed BRAF p.V600E mutations across lung, adrenal, and plasma samples, providing critical insight into the nature of the metastatic spread. Despite treatment with molecular therapy (dabrafenib + trametinib) and radiotherapy, the patient’s conditioan deteriorated rapidly, and he passed away in September 2023.DiscussionThis rare case underscores the importance of the BRAF p.V600E mutation in guiding therapy in cases of coexisting PMEC and ASC. The consistent presence of BRAF mutations in lung, adrenal, and plasma samples provided molecular evidence of the metastatic process, offering guidance for targeted therapy. Despite the potential of molecular therapy, the limited treatment efficacy suggests that further research is needed to better identify patient populations that may benefit from targeted therapies for advanced PMEC. BRAF mutations play a significant role in treatment decision-making and should be considered in clinical practice for these complex cases.ConclusionThis case highlights the complexity of diagnosing and treating coexisting low-grade PMEC and metastatic ASC, with the BRAF p.V600E mutation offering valuable molecular insights for therapy. Treatment strategies should be personalized, and future studies are needed to refine therapeutic approaches for such complex cases.